Clinical characteristics and prognostic factors of sepsis in patients with malignancy - Green Hong; Hyekyeong Ju; Dong Kyu Oh; Su Yeon Lee; Mi Hyeon Park; Haein Lee; Chae-Man Lim; Song I Lee; The Korean Sepsis Alliance (KSA) investigators (Scientific Reports)
Abstract Sepsis is a severe complication in patients with malignant tumors, leading to high mortality and increased need for intensive care. This study aimed to investigate the clinical characteristics and prognostic factors influencing sepsis outcomes in patients with malignant tumors. We included 4,858 patients with cancer diagnosed with sepsis between September 2019 and February 2020 whose data were collected from the Korean Sepsis Alliance, a nationwide multicenter cohort study. Cox regression analysis was used to identify predictors of 30-day and in-hospital mortality. In total, 65% of the patients survived, whereas 35% did not. Non-survivors were more likely to require intensive care, including mechanical ventilation and continuous renal replacement therapy. Key predictors of mortality included renal dysfunction, higher Sequential Organ Failure Assessment scores, and reliance on life-sustaining treatments. Non-survivors exhibited lower adherence to the implementation of sepsis care bundles, particularly to later-stage interventions. Gram-negative bacterial infections and multidrug resistance were more prevalent in non-survivors, complicating treatment efficacy. In conclusion, tailored treatment strategies that consider specific patient characteristics and disease dynamics are needed in managing sepsis with malignancy. Early identification and treatment of organ dysfunction, coupled with strict adherence to sepsis treatment protocols, are critical to improving survival in this population.